Revista Comunicación - Corrales Navarro, Elizabeth (Revista Comunicación, 2017)
La versión completa del número 1-2017
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTg4NDUvcmMudjI2aTEtMTcuMzMyOA